Risk Factors of Neonatal Sepsis: A Preliminary Study in Dr. Soetomo Hospital - Utomo, Martono Tri (Indonesian Journal of Tropical and Infectious Disease, 2010)
The risk factors of developing neonatal sepsis could be caused by maternal and neonatal risk factors. Objective to determine the characteristics and risk factors for neonatal sepsis. Study design was case control study. The data of neonates were taken from the medical record. Neonates who were admitted in neonatal care unit of Dr. Soetomo hospital were included at January 2010 to February 2010, and divided into 2 groups, one group was sepsis cases and other group was non sepsis cases as a control. The risk factors that associated with sepsis were studied. Chi square and logistic regression analysis were used to analyze the data. 97 patients were includedand 31were sepsis cases and non sepsis case were 66. The risk factors that significantly cause sepsis are low birth weight (p=0.001 OR 2.75, 95% CI 1.454–5.200) , prematurity (p=0.000, OR 4.073, 95% CI 2.180–7.609), meconeal amniotic fluid (p=0.029, OR 2.535,95% CI 1.225–5.245) and C-section (p=0.032, OR 1.895, 95% CI 1.087–3.303). The significant risk factors of the neonatal sepsis arelow birth weight, prematurity, meconeal amniotic fluid, and caesarian section